Potential of Wood Vinegar for Enhancing Seed Germination of Three Upland Rice Varieties by Suppressing Malondialdehyde Production - Atchima Dissatian; Jirawat Sanitchon; Paweena Pongdontri; Nuntawoot Jongrungklang; Darunee Jothityangkoon (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
Upland rice usually gives poor germination under rainfed upland environement. To improve the seed germination, seed priming technique was assessed in this study. Seed of three upland rice (Oryza sativa L.) varieties (Leum Pua, ULR038 and Sakon Nakhon1, SKN) were primed with three different seed priming agents; distilled water, CaCl2 and 300-fold diluted wood vinegar. Compared to untreated dry seeds, wood vinegar improved field emergence and improved drought tolerance of the rice seeds better than other priming agents, which 50 % for Leum Pua, 20 % for ULR038 and 16% for SKN, when watering was delayed for 7 days. All three priming agents increased the field emergence percentage by similar amounts when watering was delayed for 14 days. To understand how priming helped improvement of germination, antioxidation mechanism and sugar metabolism were examined. Level of malondialdehyde was markedly reduced in all three rice varieties in response to priming, which were associated with increased activity of antioxidant enzymes, guaiacol peroxidase and ascorbate peroxidase. Wood vinegar also accelerated amylase activity in ULR038 and SKN, but not the sugar content. The results suggest that wood vinegar is a potent priming agent for achieving rapid and uniform seed germination in upland rice.